ELECTRONIC GOVERNMENT SERVICES AND BENEFITS IN THE PRIVATE AND PUBLIC CONTEXT: A JORDANIAN CASE STUDY - MAHMOUD M. ABU ARA & MUSTAFA S. AL-SHAIKH (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
The study was selected for its theoretical and practical importance in the field of E-government services . This importance arises from that the E-government services has the potential to involve citizens in the governance process by engaging them in interaction with policymakers throughout the policy cycle and at all levels of government. The population of the study is all employees working with electronic government in Amman City in Jordan. A stratified proportional-random sample of total population is selected in order to answer the questions posed in the questionnaire. Total of (250) useable questionnaires were obtained with a response rate of (70.8%).The questionnaire consists of two parts: The first part included general data of personal variables (management level, service period, sector, gender, and age) The second part included (21) items representing benefits of E-Government services . The five- point Likert scale was used for each item in the questionnaire. Statistical Package for Social Sciences (SPSS) which is usually used in the social sciences studies was chosen to analyze the collected data. The main results and conclusions of this study are summarized as follows: There are significant statistical evidences those differences between employees in the benefits of e-government due to the following factors: management level, service period, sector, gender, and age.